Case Report: An unusual case of a transposition of the great arteries with a double aortic arch: a highly complex fetal diagnosis with an unpredictable outcome - Masci, M.; Missineo, A.; Campanale, C. M.; Moras, P.; Colucci, M. C.; Pasquini, L.; Toscano, A. (Frontiers in Cardiovascular Medicine, 2024)
Published data estimates the prevalence of VR at about 7 per 10 000 live births. The association of Double Aortic Arch with D-Transposition of the great arteries has been rarely described in literature. Fetal echocardiography at a gestational age of 24 weeks + 6 days showed D-Transposition of the great arteries and Double Aortic Arch with ventricular septal defect and pulmonary stenosis. During the first night of life, the baby developed an increase in lactate levels with oxygen saturation consistently below 80%. A few hours after birth patient underwent a Rashkind procedure. Echocardiography, CT chest, CT angiogram confirmed diagnosis with severe reduction of the tracheal lumen (>85%) and bronchomalacia. The patient underwent posterior tracheopexy and aortopexy and later an Arterial Switch Operation, ventricular septal defect closure, and resection of part of the infundibular septum, accepting the risk of potential neoaortic obstruction. The literature reported just two cases with fetal echocardiogram diagnosis. Therefore, our patient is the third one with a fetal diagnosis and the second one with complex intracardiac anatomy, characterized not only by ventricular septal defect but also by two separate components of the obstruction (a bicuspid and dysplastic valve with posterior deviation of the infundibular septum). In conclusion, D-Transposition of the great arteries with Double Aortic Arch remains an extremely unusual association. The outcome of these patients presents a high degree of variability and is entirely unpredictable in prenatal life. Our greatest expectation as fetal and perinatal cardiologists would be to improve the management and outcome of these patients through fetal diagnosis, recognizing types of congenital heart disease in newborns who require early neonatal invasive procedures.